Country Stakes in Climate Change Negotiations : Two Dimensions of Vulnerability - Buys, Piet (2012)
Future global agreements on reducing greenhouse gas (GHG) emissions are likely to include developing countries and industrialized countries that are not part of the Kyoto Protocol. An assessment using a comprehensive geo-referenced database of indicators relating to global change and energy provides insight into countries' likely attitudes and positions with respect to international treaties regulating carbon emissions. A distinction is made between source vulnerabilities (access to fossil fuels and renewable energy sources, options for GHG sequestration, the potential size of employment and income shocks) and impact vulnerabilities (changes in agricultural productivity, weather events and sea-level rise). This differential vulnerability is used to identify clear differences that determine likely negotiating positions. This helps us to understand the incentives required to make the establishment of such agreements more likely. Countries with high impact vulnerability and low source vulnerability should be the most inclined to support greenhouse gas emissions limits. Conversely, countries with high source vulnerability and low impact vulnerability should be most resistant to such limits. Additionally, a successful transition to clean energy sources will require transition support for countries with high source vulnerability and adaptation support for countries with high impact vulnerability.